Use and reuse of termite-fishing mounds by wild chimpanzees in Tanzania: An archaeological approach to perishable toolsites - Sousa, Luis Augusto Pereira Nadais de (2020)
Dissertação de Mestrado em Evolução e Biologia Humanas apresentada à Faculdade de Ciências e Tecnologia